Adaptive Mechanical Stabilization of a Free-Floating Fully Implantable Hearing Aid. Issue 9 (October 2016) - Eßinger, Till Moritz; Koch, Martin; Bornitz, Matthias; Zahnert, Thomas
Abstract : Hypothesis: An implantable acousto-mechanical transducer will yield a higher output if its mass can be virtually increased through the use of a secondary actuator. Background: Current hearing aids and implants rely on feedback compensation to prevent instability (e.g. howling), usually in the form of a digital or analogue filter. We examine the effect of mechanically stabilizing a piezo-driven mechanical amplifier inserted into the incudostapedial joint gap. The aim of this study is to determine whether this is possible and discern the advantages and disadvantages of the design. Methods: We examine a 10:1 scale model of a prospective implantable hearing aid comprising one piezoelectric sensor and two independent piezoelectric actuators in a single-titanium housing. As expected, the maximum gain of the device is limited by feedback between sensor input and the output of the primary actuator. The secondary actuator is used to provide a counter force to the recoil of the primary output piezo. This adds a virtual mass to the device, effectively reducing feedback in the mechano-acoustic path. The compensation unit (CU) described here is driven by a real-time adaptive control algorithm. Results: Using the above approach, we observe an added stable gain of >30 dB, and report a functional hearing gain of up to 40 dB. Physical and digital feedback compensation can be employed in parallel for best results. The experimental data is backed by computer simulations. Conclusion: These results compare favorably with previous studies of a two-piezo transducer with digital feedback control and show the potential for the transducer as a hearing aid for high-frequency hearing loss.